Evolution of CO2, SO2, HCl, and HNO3 in the volcanic plumes from Etna. Issue 6 (20th March 2014) - Voigt, C.; Jessberger, P.; Jurkat, T.; Kaufmann, S.; Baumann, R.; Schlager, H.; Bobrowski, N.; Giuffrida, G.; Salerno, G.
<x xml:space="preserve">Abstract</x> The volcanic plumes from degassing Etna (Italy) were extensively probed with instruments onboard the Deutsches Zentrum für Luft‐ und Raumfahrt research aircraft Falcon during the contrail, volcano, and cirrus experiment CONCERT on 29/30 September 2011. Up to 10.4 ppmv SO2and 0.3 ppmv HCl were detected with the atmospheric chemical ionization mass spectrometer AIMS at 3.1 km altitude and 20 km distance to the summit. HNO3 is the dominant reactive nitrogen component in the plumes. Linking aircraft and ground‐based observations by Hybrid Single‐Particle Lagrangian Integrated Trajectory dispersion modeling, we identify two crater plumes with different compositions primarily injected by the Bocca Nuova and North East craters. Uniquely, we follow their chemical evolution up to 5 h plume age. Our results show that CO2/SO2and SO2/HCl molar ratios are stable in the ageing plumes. Hence, conversion of SO2 to H2SO4 and partitioning of HCl in acidic plume particles play a minor role at dry tropospheric conditions. Thus, these trace gases allow monitoring volcanic activity far from the crater.